Periodontology and Dental Implantology - Manakil, Jane (IntechOpen, 2019)
Periodontology explores the molecular status in periodontal disease. Optical devices in the diagnosis and management of the disease are also discussed. The book addresses the role of the oral healthcare provider in interprofessional communication in the systemic management of autoimmune bullous disease-associated conditions. A study involving chemically modified tetracyclines and host modulation with nonsurgical and surgical periodontal therapy, including postoperative pain management, is presented here. Therapeutic strategies of stem cell application in bone tissue engineering and the potential of platelet-rich fibrin-sourced growth factors in periodontal procedures to enhance wound healing and regeneration are also proposed. Supportive implant maintenance and regenerative processes are explored. Management of the endoperiodontal lesion is also discussed (note: the recent periodontal classification has not been referenced here). The book explores the best transdisciplinary practices for the management of special healthcare needs patients.